From Journey's End - An Alumni Dramatic Production, n.d. - Munro, Melville S. (Tufts Archival Research Center, 2005)
8 x 6, mounted on 8 x 10 in: M. S. Munro, Miscellaneous pictures through the years, Vol. 1, p. 32